Inovasi Manajemen Perpustakaan dalam Meningkatkan Minat Baca di Sekolah Menengah Pertama Xaverius Santo Louis Muara Padang - Yandariani Riski; Edi Harapan; Muhammad Fahmi (Journal on Education, 2025)
This study aims to determine and describe Library Innovation Management in Increasing Reading Interest at Xaverius Santo Louis Junior High School, Muara Padang. The method used is a qualitative method. Data collection techniques use observation, interviews and documentation. The results of the study can be concluded that Library Management Innovation in Increasing Reading Interest at Xaverius Santo Louis Junior High School, Muara Padang includes planning goals, visions and missions in the form of promotions to students so that they are interested in visiting the library, in addition to planning the focus of management innovation seen from the readiness of the library in implementing in increasing student interest in visiting the library, one form of change can be seen from the infrastructure that has begun to be added and improved such as the procurement of fans, procurement of reference books, improvement of room lighting by adding lights to make it clear for students to read books in the room, the arrangement of the room layout is made more attractive, the arrangement of tables must be neat so that students are interested in reading in the library at Xaverius Santo Louis Junior High School, Muara Padang